A clinical decision instrument for head CT in intoxicated patients presenting to the emergency department: the DITCH study - Richard McNulty; Maiana Hegh; Elena Xu; Earl Butler; Naren Gunja (Toxicology Communications, 2024)
Performing head CT in intoxicated patients presenting to the emergency department (ED) is common, yet low yield. In our previous study, acute findings were found only in patients with at least one of: neurological Deficits, Intubation, Trauma, Convulsions or Headache. We hypothesise that the absence of these DITCH clinical features rules out the need for immediate CT. We collected data for intoxicated patients attending EDs in our district from March 2021 to May 2022 inclusive. We recorded clinical presentation features, agents, disposition and head CT results. There were 1,308 intoxicated patients out of a total of 219,273 ED presentations. Median age was 38 years. Common ingestions were ethanol, stimulants, GABA-ergics and opioids. 407 patients (31%) had head CT, with 31 patients (7.6%) having 36 acute findings: 19 intracranial haemorrhages, 8 fractures, 2 cerebral oedema and 7 haematomas. All patients with acute CT findings had one of the DITCH features, and all had trauma. The sensitivity and NPV of the hypothesis were 100%. In patients that were not scanned, there were no re-presentations.Our internal validation study is further evidence that acute findings on head CT in intoxicated patients presenting to the ED are only found in those who had one of the DITCH features.